Pemodelan Risiko Investasi di Indonesia - Muhammad Adnan; Zurriyani (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2022)
This study aims to analyze the effect of the interaction of internal and external factors with the global capital market index on IHSG returns in Indonesia. Using quarterly time series data for the period 2004-2018, the analytical model used consists of a cointegration test and a vector error correction model (VECM). The study found a cointegration relationship between the variables studied. Both in the long term and in the short term, the return on the MSCI ACWI IMI has no significant effect on the return on the IHSG in Indonesia.